Design of Wideband Absorber Based on Dual-Resistor-Loaded Metallic Strips - Mingxi Zhang; Binchao Zhang; Xiaochun Liu; Shining Sun; Cheng Jin (International Journal of Antennas and Propagation)
A method for designing a dual-polarized wideband absorber with low profile by using dual-resistor-loaded metallic strips is proposed in this paper. Each unit cell consists of a resistive sheet with dual-resistor-loaded metallic strips and an underlying conducting plate. Two-dimensional arrays of two unequal metallic strips are printed on the dielectric substrate, and two resistors are embedded in the metallic strips. By properly designing the resonant frequencies of these metallic strips, a wide absorption band with three resonances is obtained. An equivalent circuit model is introduced, and the current distributions are examined to understand the physical mechanism of the proposed absorber. An example of the absorber is fabricated and measured to verify our designed concept. The measured results show that the wideband absorption performance with a fractional bandwidth of 129% under the normal incidence and the stable angular response are achieved. In addition, the proposed absorber has a low profile with 0.08λL, where λL is the wavelength at the lowest operating frequency.